1975
DOI: 10.1002/bms.1200020502
|View full text |Cite
|
Sign up to set email alerts
|

Environmental applications of mass spectrometry

Abstract: Publications from 1969 through 1974 reporting organic and spark source mass spectrometric studies on environmental samples have been compiled. Emphasis is placed on pollutants identified, but some methods and techniques are discussed. The 396 reports cited vary from those reporting hundreds of identified pollutants to those describing the analysis of only one sample containing one or a few pollutants. Reports concerning forensic, synthetic and standard samples, and analyses for drug residues. metabolites and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 264 publications
0
4
0
Order By: Relevance
“…Although the characterization of a few individual substances of the environment has, upon occasion, been given primary emphasis [e.g., dimethylnitrosamine (1, 2), pesticides (3,4), polynuclear aromatic hydrocarbons (5-7)] a comprehensive identification of all pollutants present in environmental matrices (air, water, food) would be desirable in understanding man's exposure to toxic chemicals. This approach presents a formidable task, because these media are very complex chemical mixtures, with many constituents present at trace levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the characterization of a few individual substances of the environment has, upon occasion, been given primary emphasis [e.g., dimethylnitrosamine (1, 2), pesticides (3,4), polynuclear aromatic hydrocarbons (5-7)] a comprehensive identification of all pollutants present in environmental matrices (air, water, food) would be desirable in understanding man's exposure to toxic chemicals. This approach presents a formidable task, because these media are very complex chemical mixtures, with many constituents present at trace levels.…”
Section: Introductionmentioning
confidence: 99%
“…Hypobromite may be converted to molecular bromine at pH 4, and bromine may be lost to the atmosphere by volatilization (5,6). Carpenter et al (3) suggested that hypobromite may oxidize iodide not only to triiodide but also to iodate: 3BrO" + -I03-+ 3BrS ince iodate does not react directly with phenylarsine oxide and, at pH 4, the reaction between iodate and iodide to form triiodide is sluggish, any iodate that has not been convertd to triiodide will be considered a disappearance of the added chlorine. Crecelius et al (4) reported that this problem may be circumvented by premixing the pH 4 buffer and the iodide solution in the titration vessel prior to the addition of the sample and subsequent titration with phenylarsine oxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous reviews have been published that included environmental applications of mass spectrometry. Historical examples of reviews include ones by Alford, Freudenthal, Keith, Safe, and Schulten published in the 1970s and ones by Dougherty, , Cairns et al, , and Bursey and Hass in the early 1980s. These reviews covered general reviews of environmental mass spectrometry applications, field-ionization and field-desorption-MS, NCI-MS, and tandem mass spectrometry 36 and reviews of mass spectrometry applied to specific analytes, such as dioxins, pesticides, and industrial chemicals …”
Section: General Reviewsmentioning
confidence: 99%